Pelatihan Pembuatan dan Pengemasan Produk Kripik Jagung di Desa Seberang Kecamatan Amali Kabupaten Bone - A.Besse Dahliana; Hujemiati Hujemiati; Hasmidar Hasmidar; Jumardi Jumardi; Faisal Faisal (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The KKLP activity carried out by STIP Yapi Bone students is also a community service activity by providing training on the manufacture and packaging of corn chip products in the village across Amali District, Bone Regency.This activity aims to increase understanding to the community as MSME actors about the importance of packaging in products in order to attract consumers to buy products, as well as provide training to MSME actors on how to make good and attractive product packaging, in addition to providing training on how to manufacture corn chips products worth selling and delicious on the tongue. Seeing the majority of the villagers across the street as corn farmers, this attracted our attention to provide training on the manufacture and packaging of corn chips, with the aim that the economy of the community in Sebereng village could improve and so that people who did not have permanent jobs could start businesses as sellers of corn chips.